Vocabulary selection and translation of China's Report on the Work of the Government: a case study of “considerably” “noticeably” & “resolutely” from their semantic prosody performance - Ma, Guangyao; Husain, Salina; Wan Sulong, Wan Muhammad (Sciedu Press, 2025)
This research studied vocabulary selection and translation of China’s Report on the Work of the Government (RWG) from the perspective of semantic prosody (SP). “noticeably”, “considerably” & “resolutely” were adopted to give a case study with the help of corpus tools under the theoretical guidance of Corpus-based Translation Studies (CBTS) and Critical Discourse Analysis (CDA). The RWG corpus was compared with the British National Corpus (BNC) in emotion color and pragmatic meaning. Major findings include that there are similarities and conflicts in terms of the SP performance of three adverb words in the two corpora. Instead of following the mainstream SP shown by the BNC, “noticeably” “considerably” & “resolutely” met purposes of language use and political communication, and gave an impact on lexical selection and translation. For political considerations, employed as translation words in the RWG, “noticeably” “considerably” & “resolutely” strongly demonstrate that the Chinese government was dedicated to delivering China’s voice and building a good national image in China’s Report on the Work of the Government.